ПРОБЛЕМНОЕ ОБУЧЕНИЕ КАК СРЕДСТВО РАЗВИТИЯ ШКОЛЬНОГО ОБРАЗОВАНИЯ - Бектурганова, З.К.; Кожамуратова, А.А.; Калыбаева, У.Т.; Хасанова, М.К. (SCIENCE and SOCIETY, 2019)
The article examines the problematic processes of broad and multifaceted development of school children, the problems in the field of school education, the problem extention of the world view of perception of skills of the subjects taught at the general educational shools..